2001
DOI: 10.1021/jm0102147
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic Effects of Human Cyclic MBP87-99Altered Peptide Ligands in Experimental Allergic Encephalomyelitis and Human T-Cell Proliferation

Abstract: The immunodominant myelin basic protein (MBP) peptide comprising residues 87-99 is a self-antigen in multiple sclerosis (MS). In Lewis rats this epitope induces experimental allergic encephalomyelitis (EAE), a demyelinating disease of the central nervous system, and is a model of MS. Structure-activity studies have shown that Lys(91) and Pro(96) residues are important for encephalitogenicity. Replacement of Lys and/or Pro residues with Arg and/or Ala, respectively, results in suppression of EAE. A potent linea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
120
0
5

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 80 publications
(125 citation statements)
references
References 49 publications
0
120
0
5
Order By: Relevance
“…By binding directly to MHC in the absence of costimulation, they are expected to induce tolerance to the epitope. Some groups have attempted to increase stability of the tolerizing peptide by circularising it or changing key residues to eliminate proteolytic cleavage sites (Burster et al 2007b;Tselios et al 2002).…”
Section: Future Trends and Therapiesmentioning
confidence: 99%
“…By binding directly to MHC in the absence of costimulation, they are expected to induce tolerance to the epitope. Some groups have attempted to increase stability of the tolerizing peptide by circularising it or changing key residues to eliminate proteolytic cleavage sites (Burster et al 2007b;Tselios et al 2002).…”
Section: Future Trends and Therapiesmentioning
confidence: 99%
“…We incubated Mu20 with human blood serum for 24 h and found that Mu20 was stable from degradation by protease activity, suggesting a prolonged stability during in vivo use (data not shown). [26]. These cyclic analogues demonstrated less protease-resistance when lysosomal proteases from THP-1 were used as compared to the linear protease-resistant peptides synthesized by the method described here (data not shown).…”
Section: Discussionmentioning
confidence: 69%
“…Effort must be made to understand: (a) the forces that determine the folding of the epitope; (b) the conservation of the linearity and extended structure of the altered epitope; (c) the molecular features of the altered epitope that maximize the productive interactions with HLA-DR2 and minimize the contacts with TCR. The linear peptides were prepared on 2-chlorotrityl chloride resin (CLTR-Cl) using the Fmoc/tBu solid-phase methodology [28][29][30][31]. The first N a Fmoc (9-fluorenylmethyloxycarboxyl)-protected amino acid (Fmoc-Pro-OH) was esterified to the resin in the presence of diisopropylethylamine (DIPEA) in dichloromethane (DCM) in 1 h at RT [28][29][30][31].…”
Section: Resultsmentioning
confidence: 99%
“…The linear peptides were prepared on 2-chlorotrityl chloride resin (CLTR-Cl) using the Fmoc/tBu solid-phase methodology [28][29][30][31]. The first N a Fmoc (9-fluorenylmethyloxycarboxyl)-protected amino acid (Fmoc-Pro-OH) was esterified to the resin in the presence of diisopropylethylamine (DIPEA) in dichloromethane (DCM) in 1 h at RT [28][29][30][31]. DCM/MeOH/DIPEA (85:10:5) was then added and the resulting mixture was stirred for another 10 min at RT.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation